Feasibility of Using iTIVA™ Mobile Application as Intraoperative Infusion Guide in Pediatric - Olivia, Wilhemina; Pramodana, Bintang (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Background: Total intravenous anaesthesia (TIVA) is increasingly popular in pediatric anaesthesia. TIVA can be given with manual or target-controlled infusion (TCI). TCI pumps with specialized pediatric pharmacokinetic (PK) models are not widely available. iTIVA is a mobile application that simulates TCI infusion regiments with many available PK models, including pediatric. The app is available for download for iOS and Android devices. We report our experience using iTIVA as an intraoperative infusion guide. Case illustration: A 12-year-old boy with body weight of 53 kg and 153 cm tall, physical status ASA II, presented with tethered cord syndrome due to lipomyelomeningocele planned for untethering surgery. Anaesthesia was induced and maintained with TIVA using propofol with Eleveld model using Mindray TCI pump and remifentanil using Eleveld model simulated with iTIVA apps. The initial target, desired plasma or effect concentration were selected, and the application determined the required infusion rates for remifentanil. The Bispectral Index System (BIS) was used to monitor the depth of anaesthesia. There were no adverse events observed during the surgery. The patient was then transferred to the recovery room and discharged from the hospital on the second postoperative day. Conclusion: iTIVA can be useful to simulate TCI infusion regiments if specialized TCI pumps are unavailable.